Strategic Framework for Enhancing Youth Leadership in Community-Based Waste Management: A Case Study of Bangka Regency, Indonesia - Widya Handini; Darol Arkum (Pencerah, 2026)
This study examines the level of youth participation in community-based waste management and develops a strategic framework to strengthen youth leadership in sustainable waste governance in Bangka Regency, Indonesia. A qualitative descriptive approach was employed using in-depth interviews, participant observation, and document analysis. Informants were selected purposively from youth organizations, local government agencies, environmental organizations, community representatives, and academics. Data were analyzed thematically using Arnstein’s Ladder of Citizen Participation. The findings indicate that youth actively participate in environmental campaigns, waste bank management, and community clean-up activities. However, their involvement remains largely operational, with limited participation in planning, policy formulation, and environmental decision-making. Based on Arnstein’s framework, youth participation is categorized as tokenism, reflecting visible engagement without meaningful influence over governance processes. The study identifies weak institutional recognition, limited leadership capacity, fragmented stakeholder collaboration, inadequate access to strategic information, and insufficient long-term support as the main barriers to meaningful participation. This study proposes a Strategic Framework for Transforming Youth Leadership in Sustainable Waste Governance, integrating institutional integration, capacity development, multi-stakeholder collaboration, information transparency, and sustainable incentive mechanisms.